Mutual aid for domestic purposes: one way of child labor through socio-family networks - Sandoval Figueroa, Carmen María (2018)
This article deals with forms of children’s inclusion in domestic child labour through their socio-familial networks. These minors describe the work they perform as a kind of mutual help with domestic purposes, so that the minor supports a relative or acquaintance in domestic chores. Both children and their relatives base these exchanges on the system of mutual help between relatives and acquaintances, and the placement of the minor is based on trust between the actors. The article presents three forms of children inclusion in domestic child labour through socio-familial chains: (1) by affective and residential proximity, (2) by ties of kinship by choice, and (3) by consanguineous kinship ties. Mutual aid for domestic purposes is a practice that children perform prior to engaging in domestic child labour carried out for third-party families.